Dimensi, Jenjang dan Asesmen Perilaku Berliterasi Siswa di Sekolah - Suyono Suyono (Jurnal Ilmu Pendidikan, 2016)
Dimensions and stages of student literacy behavior at schools should ideally cover the awareness and motivation, skill, and interest in literacy and maintenance of these aspects in the actualization of literacy behavior. In this way, the activities of reading, thinking and writing as the core of literacy behavior can be fully developed on a high level of awareness and motivation, which will be manifested in the interest shown by students in their daily activites at school. Futhermore, students will be motivated to work hard to maintain their achievement. Therefore assessment of the students literacy should be congruent with the dimention and stages of the ideal literacy behavior.